1974
DOI: 10.1111/j.1365-2222.1974.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological and allergic features of asthma in the New Guinea Highlands

Abstract: Summary Asthma in the New Guinea Highlands is of interest because of its reported rarity. In the Eastern Highlands, seventy‐one cases of asthma were investigated over a 12 month period. In addition, a whole village community of 2000 people was examined for wheezing illness. In children and adolescents asthma was extremely uncommon with no case being identified in the community study and the youngest hospital case being 10 years old. The prevalence of active asthma in adults was estimated to be 0.2–0.3%. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 21 publications
7
56
1
1
Order By: Relevance
“…In Papua New Guinea, ANDERSON [78] observed that respiratory infections were more common among young children in the Highlands, where the asthma rate was exceedingly low as compared to the coastal regions of the country where asthma occurred more frequently. In the Fiji Islands, FLYNN [79,80] studied two groups of children, the indigenous Fijians who showed a high hospital admission rate for pneumonia and the Fiji Indians whose asthma admission rate was three times higher than in the Fijians.…”
Section: Other Infections Of the Respiratory Tractmentioning
confidence: 99%
“…In Papua New Guinea, ANDERSON [78] observed that respiratory infections were more common among young children in the Highlands, where the asthma rate was exceedingly low as compared to the coastal regions of the country where asthma occurred more frequently. In the Fiji Islands, FLYNN [79,80] studied two groups of children, the indigenous Fijians who showed a high hospital admission rate for pneumonia and the Fiji Indians whose asthma admission rate was three times higher than in the Fijians.…”
Section: Other Infections Of the Respiratory Tractmentioning
confidence: 99%
“…Another change in lifestyle that may have led to an introduction of house dust mites into sleeping quarters is the replacement of the traditional floor mats by blankets and mattresses. This has been offered as an explanation for the relatively sudden increase in asthma in all ages in Papua New Guinea from 0.9% in 1972 [12] to 7.3% in 1984 [13]. Urban studies in Kenyan adults [14] and Tanzanian children [15] show that asthma patients exhibit a high A respiratory health and home environment questionnaire was administered at school to parents or guardians.…”
Section: Aamentioning
confidence: 99%
“…About one-fifth of Highland asthmatics investigated, however, had additional symp-toms of chronic cough and might, for this reason, have been also classified as CLD. These cases were 12 years older at the onset of asthma (mean onset age 40) but otherwise resembled other asthmatics rather than the CLD group in terms of sensitivity to allergens (100% positive), sputum histology, and variability of FEV1 (Anderson, 1974b). Lung volumes were consistent with obstruction and the Ti was normal.…”
Section: Discussonmentioning
confidence: 89%
“…Subjects whose main complaint was episodic wheezing were classified as asthma, and these are described elsewhere (Anderson, 1974b (Meade et al, 1965) the total lung capacity (TLC), functional residual capacity (FRC), and residual volume (RV) were measured by the steady state helium method, and the transfer factor (TI) was measured by the single breath method. The mixed venous carbon dioxide tension (PMco2) was estimated by the rebreathing method of Campbell and Howell (1962).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation